A long-lived fluorenyl cation: efficiency booster for uncaging and photobase properties. Issue 9 (17th February 2022) - Abdellaoui, Chahinez; Hermanns, Volker; Reinfelds, Matiss; Scheurer, Maximilian; Dreuw, Andreas; Heckel, Alexander; Wachtveitl, Josef
Abstract : The symmetric dimethylamino-fluorene proved to be a more efficient photolabile protecting group than non-symmetric analogue. This is due to the long-lived fluorenyl cation intermediate, which also enables application as hydroxide emitting photobase. Abstract : The photochemistry of fluorenols has been of special interest for many years. This is because both the fluorenol and the fluorenyl cation are antiaromatic in the ground state due to their 4n π-electrons according to the Hückel rule. The photolysis reaction of various fluorene derivatives takes place via a cation intermediate and is preferred due to its excited state aromaticity. Here we present an extremely long-lived fluorenyl cation and its effects on the uncaging of various leaving groups. We analyze the relationship between uncaging quantum yields of fluorene-based cages and the longevity of their fluorenyl cations with different spectroscopic methods in the steady state and on an ultrafast time scale and find that the uncaging quantum yield rises with the stability of the cation. In contrast to previous reports, the cation can be observed on a time scale of minutes, even in moderately protic solvents as methanol and ethanol. The stability of this cation depends on the dimethylamino-substituents on the fluorene scaffold and the properties of the solvent. In addition, with bis-dimethylamino fluorenol, a photobase is introduced that expands the small group of known photoinduced hydroxide emitters.